Gentamicin Rapidly Inhibits Mitochondrial Metabolism in High-Frequency Cochlear Outer Hair Cells - Jensen-Smith, Heather C.; Hallworth, Richard; Nichols, Michael G. (PLOS ONE, 2012)
Aminoglycosides (AG), including gentamicin (GM), are the most frequently used antibiotics in the world and are proposed to cause irreversible cochlear damage and hearing loss (HL) in 1/4 of the patients receiving these life-saving drugs. Akin to the results of AG ototoxicity studies, high-frequency, basal turn outer hair cells (OHCs) preferentially succumb to multiple HL pathologies while inner hair cells (IHCs) are much more resilient. To determine if endogenous differences in IHC and OHC mitochondrial metabolism dictate differential sensitivities to AG-induced HL, IHC- and OHC-specific changes in mitochondrial reduced nicotinamide adenine dinucleotide (NADH) fluorescence during acute (1 h) GM treatment were compared. GM-mediated decreases in NADH fluorescence and succinate dehydrogenase activity were observed shortly after GM application. High-frequency basal turn OHCs were found to be metabolically biased to rapidly respond to alterations in their microenvironment including GM and elevated glucose exposures. These metabolic biases may predispose high-frequency OHCs to preferentially produce cell-damaging reactive oxygen species during traumatic challenge. Noise-induced and age-related HL pathologies share key characteristics with AG ototoxicity, including preferential OHC loss and reactive oxygen species production. Data from this report highlight the need to address the role of mitochondrial metabolism in regulating AG ototoxicity and the need to illuminate how fundamental differences in IHC and OHC metabolism may dictate differences in HC fate during multiple HL pathologies.